REV1 and polymerase ζ facilitate homologous recombination repair - Sharma, Shilpy (Oxford University Press, 2012)
REV1 and DNA Polymerase ζ (REV3 and REV7) play important roles in translesion DNA synthesis (TLS) in which DNA replication bypasses blocking lesions. REV1 and Polζ have also been implicated in promoting repair of DNA double-stranded breaks (DSBs). However, the mechanism by which these two TLS polymerases increase tolerance to DSBs is poorly understood. Here we demonstrate that full-length human REV1, REV3 and REV7 interact in vivo (as determined by co-immunoprecipitation studies) and together, promote homologous recombination repair. Cells lacking REV3 were hypersensitive to agents that cause DSBs including the PARP inhibitor, olaparib. REV1, REV3 or REV7-depleted cells displayed increased chromosomal aberrations, residual DSBs and sites of HR repair following exposure to ionizing radiation. Notably, cells depleted of DNA polymerase η (Polη) or the E3 ubiquitin ligase RAD18 were proficient in DSB repair following exposure to IR indicating that Polη-dependent lesion bypass or RAD18-dependent monoubiquitination of PCNA are not necessary to promote REV1 and Polζ-dependent DNA repair. Thus, the REV1/Polζ complex maintains genomic stability by directly participating in DSB repair in addition to the canonical TLS pathway.